CONSTITUTIONAL REFORMS – A MOVEMENT FOR HUMAN DIGNITY (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2025)
This article analyzes the essence and significance of the constitutional reforms being implemented in the Republic of Uzbekistan, particularly their role in enhancing human dignity, honor, and rights. It also examines the role of the principle “For Human Dignity” in the new version of the Constitution and explains the substance of reforms aimed at democratizing relations between the state and society.